THE APPLICATION OF THE STAD TYPE OF COOPERATIVE LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF FOURTH-GRADE STUDENTS AT SDN RAWU SERANG CITY - Enah Suhaenah; Sholeh Hidayat; Lukman Nulhakim (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractThis research aims to determine the increase in student learning outcomes in Mathematics of fourth-grade students at SDN Rawu Serang City, 2020/2021 academic year with the STAD type of cooperative learning model. This research is a classroom action research which is conducted in two cycles. Each cycle consists of four stages, namely: planning, implementation, evaluation, and reflection. The research subjects were 40 fourth-grade students at SDN Rawu Serang City of 2020/2021 academic year. The data collection in this study was carried out by the test method of the critical thinking ability. Furthermore, the data were analyzed using the formula of quantitative descriptive analysis techniques. The results of this research indicate that the application of the STAD type of cooperative approach can improve mathematics learning outcomes in the fourth-grade Mathematics subject at SDN Rawu Serang City in the 2020/2021 academic year. It can be seen that the average result of students’ ability in the first cycle increased by 13% and the average result of students ability in the second cycle increased by 17%. Meanwhile, the students learning outcomes have increased as seen from the second post-test result which obtained a score of 80.5 with the high category. So the conclusion of this research is that the application of a cooperative approach of student teams achievement division (STAD) type can increase students’ learning outcomes in Mathematics of fourth-grade students at SDN Rawu Serang City of 2020/2021 academic year.Kata Kunci: STAD Cooperative Learning Model; Learning Outcomes